Redefining bacterial origins of replication as centralized information processors - Marczynski, Gregory T.; Rolain, Thomas; Taylor, James A. (Frontiers in Microbiology, 2015)
In this review we stress the differences between eukaryotes and bacteria with respect to their different cell cycles, replication mechanisms and genome organizations. One of the most basic and underappreciated differences is that a bacterial chromosome uses only one ori while eukaryotic chromosome uses multiple oris. Consequently, eukaryotic oris work redundantly in a cell cycle divided into separate phases: First inactive replication proteins assemble on eukaryotic oris, and then they await conditions (in the separate “S-phase”) that activate only the ori-bound and pre-assembled replication proteins. S-phase activation (without re-assembly) ensures that a eukaryotic ori “fires” (starts replication) only once and that each chromosome consistently duplicates only once per cell cycle. This precise chromosome duplication does not require precise multiple ori firing in S-phase. The single bacterial ori has no such margin for error and a comparable imprecision is lethal. Single ori usage is not more primitive; it is a totally different strategy that distinguishes bacteria. We further argue that strong evolutionary pressures created more sophisticated single ori systems because bacteria experience extreme and rapidly changing conditions. A bacterial ori must rapidly receive and process much information in “real-time” and not just in “cell cycle time”. This redefinition of bacterial oris as centralized information processors makes at least two important predictions: First that bacterial oris use many and yet to be discovered control mechanisms and second that evolutionarily distinct bacteria will use many very distinct control mechanisms. We review recent literature that supports both predictions. We will highlight three key examples and describe how negative-feedback, phospho-relay and chromosome-partitioning systems act to regulate chromosome replication. We also suggest future studies and discuss using replication proteins as novel antibiotic targets.